A RISK ANALYSIS OF OCCUPATIONAL SAFETY LEVELS FOR OPERATORSON COMPANY X USING A HAZOP METHOD WITH AN FTA APPROACH - Irfan Ramdani; MuhRiky Firdaus; Ricky Yasten Fahik; Zidan Lazuardi; Yani Iriani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Company X is a manufacturer of airplanes and helicopters that also offers aircraft engines inspection. In an effort to execute its business goals, company X on behalf of its production division owns a lower or an airplane wing process where the division faces extremely high potential risks. The purpose of this study is to identify and analyze the problems faced by Company X. HAZOP and FTA were two methods employed in this research. According to the research findings by means of HAZOP, 8 potential hazards were figured out with 1 low-risk problem, 2 medium-risk problems, 4 high-risk problems, and 1 extreme-risk problem. While, by means of the FTA method, the results revealed 4 problems that are categorized as basic events. The emersion of the troubles is due to the poor lightings. All in all, it is hoped that this study can be a recommendation and offer the company way of betterment in terms of the system.